Genetic relationships and low diversity among the tea-oil Camellia species in Sect. Oleifera, a bulk woody oil crop in China - Qi, Huasha; Sun, Xiuxiu; Yan, Wuping; Ye, Hang; Chen, Jiali; Yu, Jing; Jun, Dai; Wang, Chunmei; Xia, Tengfei; Chen, Xuan; Li, Dongliang; Zheng, Daojun (Frontiers in Plant Science, 2020)
Tea-oil Camellia is one of the four woody oil crops in the world and has high ecological, economic and medicinal values. However, there are great differences in the classification and merging of tea-oil Camellia Sect. Oleifera species, which brings difficulties to the innovative utilization and production of tea-oil Camellia resources. Here, ISSR, SRAP and chloroplast sequence markers were analyzed in 18 populations of tea-oil Camellia Sect. Oleifera species to explore their phylogenetic relationships and genetic diversity. The results showed that their genetic diversity were low, with mean H and π values of 0.16 and 0.00140, respectively. There was high among-population genetic differentiation, with ISSR and SRAP markers showing an Fst of 0.38 and a high Nm of 1.77 and cpDNA markers showing an Fst of 0.65 and a low Nm of 0.27. The C. gauchowensis, C. vietnamensis and Hainan Island populations formed a single group, showing the closest relationships, and supported being the same species for them with the unifying name C. drupifera and classifying the resources on Hainan Island as C. drupifera. The tea-oil Camellia resources of Hainan Island should be classified as a special ecological type or variety of C. drupifera. However, cpDNA marker-based STRUCTURE analysis showed that the genetic components of the C. osmantha population formed an independent, homozygous cluster; hence, C. osmantha should be a new species in Sect. Oleifera. The C. oleifera var. monosperma and C. oleifera populations clustered into two distinct clades, and the C. oleifera var. monosperma populations formed an independent cluster, accounting for more than 99.00% of its genetic composition; however, the C. oleifera populations contained multiple different cluster components, indicating that C. oleifera var. monosperma significantly differs from C. oleifera and should be considered the independent species C. meiocarpa. Haplotype analysis revealed no rapid expansion in the tested populations, and the haplotypes of C. oleifera, C. meiocarpa and C. osmantha evolved from those of C. drupifera. Our results support the phylogenetic classification of Camellia subgenera, which is highly significant for breeding and production in tea-oil Camellia.